DRUG METABOLISM BY WHITE ROT FUNGI AND BROWN ROT FUNGI - D.R. MAJUMDER; AKSHAY JOSHI; DANIYA KAZI; ULFAT SAYYED (International Journal of Pharma and Bio Sciences, 2016)
Biotransformation is the chemical modification/alteration of chemical compounds like amino acids, toxins, xenobiotic and drugs brought by an enzyme or an enzyme system of an organism to produce bioactive molecules were selected. Biotransformation of Diclofenac, Paracetamol and Aspirin (1% w/v) concentration of each by Basidiomycetes,Gleophyllum sp Brown rot fungi and Agaricus sp White rot fungi were studied. The said drugs are the most commonly used by human and have adverse effect on ecosystem when excreted. Post biotransformation metabolites of drugs were checked by TLC and HPLC. From the results of TLC and HPLC the metabolites of Paracetamol matched with Hydroquinone and Glutathione disulphide, metabolites of Diclofenac found to be 4-hydroxy diclofenac and unknown D2 and for Aspirin metabolites matches with Gentisic acid and unknown A2.Thus, Fungal biotransformation of the above mentioned drugs to less /nontoxic metabolite is an ecofriendly approach.